Transformasi Digital Pedagogi Pascasarjana: Mengembangkan Sistem Pembelajaran yang Dipersonalisasi Berdasarkan Preferensi Pembelajaran Individu - Azizatul Khairi; Rambat Nur Sasongko; Ijayani Ijayani; Nur Fathanah; Aldian Mapsur Putra (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
This study aims to analyse postgraduate students' learning style preferences based on the VARK model. The study used a quantitative, descriptive survey design. The population in this study comprised all 95 active students in the Postgraduate Program in Educational Administration, and a sample of 72 respondents was selected using purposive random sampling, with a 5% margin of error. Data were collected through a 16-item questionnaire. The data were then analyzed using descriptive statistics, such as percentages and category distributions, to describe the tendencies of students' learning styles, whether unimodal (V, A, R, or K), bimodal (VA, VR, VK, AR, AK, and RK), trimodal (VAR, VAK, VRK, and ARK), or quadmodal (VARK). The results of the study indicate that graduate students predominantly prefer multimodal learning styles, particularly quadmodal (VARK), with 47.22% selecting this style. Multimodal, flexible postgraduate learning strategies accommodate the diversity of student learning preferences and enhance the quality and effectiveness of the learning process. An inclusive, multimodal postgraduate learning approach is conceptually important for accommodating the diversity of student learning preferences.